UJI KUALITAS AIR SUNGAI GEMPOLSARI DI SEKITAR LUMPUR LAPINDO DENGAN PARAMETER FISIKA-KIMIA UNTUK MENENTUKAN STATUS MUTU LINGKUNGAN - Izzy Eka Nur Rochmad; Naja Suad Suzainti; Abellya Syafira; Rizky Alicia Miranti; Rusmini (Department of Chemistry, Faculty of Mathematics and Natural Sciences, Surabaya State University, located at Jl Ketintang, Surabaya, East Java, Indonesia, 2025)
Water is a resource that is vulnerable to quality degradation due to anthropogenic activities and environmental disasters. The Lapindo mudflow that has been occurring since 2006 in Sidoarjo has the potential to affect the condition of surrounding waters, including the Gempolsari River, which is located near the affected area. This study aims to analyze the water quality of the Gempolsari River using physical-chemical parameters as a basis for determining environmental quality status. The methods used included water sampling and analysis of selected parameters, namely pH, DO, TDS, nitrate (NO3-), ammonia (NH3), and heavy metals. The analysis was carried out using simple field test equipment and compared with river water quality standards based on Government Regulation No. 22 of 2021. The results showed that the nitrate level was 50 mg/L, which exceeded the threshold, indicating nutrient pollution. Other parameters such as ammonia (0 mg/L), most heavy metals (0 mg/L), pH (7.5), TDS (0.308 mg/L), and DO (10 mg/L) were still within the quality standards. However, the concentrations of magnesium (425 mg/L) and carbon (425 mg/L) were detected to exceed the standards. These findings indicate that the water quality of the Gempolsari River is relatively good for most parameters, but is lightly to moderately polluted due to nutrient loads, particularly nitrates, and certain mineral content. Overall, this study emphasizes the importance of continuous monitoring of water quality in the areas affected by the Lapindo mudflow. The results can be used as a basis for environmental management recommendations and pollution mitigation efforts for the sake of aquatic ecosystem sustainability and public health protection.